Reformulasi Teoretis Konsep Kebatalan Keputusan Administrasi Pemerintahan dalam Undang-Undang Administrasi Pemerintahan - Efendi, A'an; Sudarsono, Sudarsono; Edwinarta, Caesar Dimas; Musthafa, Annas Rasid (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2024)
The two types of invalidity of administrative acts in the Government Administration Law, which include invalid and voidable, are not in accordance with the concept of invalidity in administrative law. The aim of this research is to find answers to two problems, first, the concept of administrative acts in the Government Administration Law, and second, the correct meaning regarding the invalidity of decisions based on the concepts and principles of administrative law. Using a doctrinal type of legal research with a legislation approach and a conceptual approach, this research produces two conclusions. First, the concept of decision in the Government Administration Law is a decision in a broad sense including general case decisions (besluit) and individual case decisions (beschikking) including factual actions, and the latter is not appropriate. Second, the nullity of administrative acts in administrative law includes being null and void and voidable, firstly the decision and its legal consequences are deemed to have never existed, secondly the decision and its legal consequences are valid until they are annulled by a later decision or administrative court.